The forum on China-Africa cooperation (focac): a framework for China’s re-engagement with Africa in the 21st Century. - Chuka Enuka (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2011)
This article offers an examination of FOCAC as a framework for Sino-African engagement in the 21st Century. China‟s growing and expanding engagement with Africa has assumed a prominent feature of International Relations and discourses. The engagement is multifaceted, encapsulating mainly trade and related economic ties. Given China‟s fast economic and industrial growth, thirst and huge demand for new sources of energy and other resources has been generated, bringing China closer to Africa where the availability of these resources abound. This situates China‟s renewed interest in Africa since the 21st Century. The deepening of economic involvement in Africa is realized through a mix of aid,special concessions, debt relief, scholarships, the provision of educational and medical training personnel and infrastructural investment projects. This represents a stark departure from the past under Mao Zedong, when the relationship was guided by the ideological conflict of the Cold War and especially Beijing‟s attempts to dislodge Moscow‟s influence in the Third World. Now economic pragmatism and symbolic diplomacy appear to navigate Sino-African relations. The lynchpin of China‟s re-engagement of African in this century is the Forum on China-Africa Cooperation (FOCAC), initiated at the Ministerial Conference in Beijing in 2000. The article explores the FOCAC framework, assesses the reality of its promises, and addresses the question of its problems and challenges. The findings are that China‟s increased presence in Africa under the FOCAC framework has been faced with criticisms and confrontations, but the forum has equally strengthened bilateral economic relationship between China and Africa, and has provided platform for Beijing to become a serious humanitarian benefactor to Africa.